2000
DOI: 10.1046/j.1570-7458.2000.00709.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐ and post‐landing response of the parasitoid Encarsia formosa to whitefly hosts on Gerbera jamesonii

Abstract: One of the factors that may complicate biological control of the greenhouse whitefly on Gerbera jamesonii by Encarsia formosa is the rosette shape of this ornamental, which differs from the vertical shape of most vegetable plants (cucumber, egg plant, tomato, etc.). Therefore, host-habitat location and the behaviour prior to landing on uninfested and infested leaves was studied. Attraction of E. formosa from a short distance by infested leaves could not be detected: the parasitoid females landed at random on u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…It is well established that parasitoids and predators use herbivore-induced plant volatiles to locate their herbivorous hosts or prey (Vet and Dicke, 1992;Steidle and van Loon, 2003). However, several studies showed that E. formosa does not (Noldus and van Lenteren, 1990;Sütterlin and van Lenteren, 2000;Romeis and Zebitz, 1997;van Roermund and van Lenteren, 1995;van Lenteren et al, 1976; but see Birkett et al, 2003). Rodriguez-Saona et al (2003) found that plants infested by the silverleaf whitefly emitted plant volatiles similar to undamaged plants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well established that parasitoids and predators use herbivore-induced plant volatiles to locate their herbivorous hosts or prey (Vet and Dicke, 1992;Steidle and van Loon, 2003). However, several studies showed that E. formosa does not (Noldus and van Lenteren, 1990;Sütterlin and van Lenteren, 2000;Romeis and Zebitz, 1997;van Roermund and van Lenteren, 1995;van Lenteren et al, 1976; but see Birkett et al, 2003). Rodriguez-Saona et al (2003) found that plants infested by the silverleaf whitefly emitted plant volatiles similar to undamaged plants.…”
Section: Discussionmentioning
confidence: 99%
“…Nymphs were carefully transferred from their original feeding site onto the leaflets. Previous experiments revealed that parasitoids still accept transferred nymphs for both oviposition and host feeding, and that E. formosa does not exploit herbivore-induced plant volatiles to locate hosts from a distance (Noldus and van Lenteren, 1990;Romeis and Zebitz, 1997;Sütterlin and van Lenteren, 2000). Only fourth nymphal stages were used because younger stages are easily damaged during transfer.…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies, an effect of trichomes on natural enemies was detectable only at high prey/host densities (e.g., Sutterlin and van Lenteren 2000) while in other studies such an effect was observed only at low densities (Krips et al 1999). …”
Section: Effects On Tritrophic Interactionsmentioning
confidence: 95%
“…In this study, it is not known whether trichomes increase the survival and performance of leafminer larvae. However, Sü tterlin and van Lenteren (2000) reported that trichomes hinder host-searching behaviours of parasitoids and lower the parasitism rate of leafminers. In addition, trichomes could indirectly raise survival of leafminer larvae by reducing leaf damage by ectophagous herbivores.…”
Section: Relations Between Leaf Traits and Herbivore Attacksmentioning
confidence: 99%